A TGF-loading hydrogel scaffold capable of promoting chondrogenic differentiation for repairing rabbit nasal septum cartilage defect - Zhang, Dan; Su, Ying; Sun, Peng; Liu, Xingzhi; Zhang, Lin; Ling, Xuwei; Fan, Yuhui; Wu, Kang; Shi, Qin; Liu, Jisheng (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogel-based tissue engineering has been widely used to repair cartilage injury. However, whether this approach can be applied to treat nasal septum cartilage defects remains unclear. In this study, three gelatin methacrylate-based scaffolds loaded with transforming growth factor (TGF)-β1 (GelMA-T) were prepared, and their repair effect on nasal septum cartilage defects was examined. In vitro, the GelMA-T scaffolds showed good biocompatibility and promoted the chondrogenic differentiation of bone mesenchymal stem cells (BMSCs). Among three scaffolds, the 10% GelMA-T scaffolds most effectively promoted chondrogenic differentiation, which significantly improved the expression of chondrocyte-related genes, including Col II, Sox9 and ACAN. In vivo, 10% GelMA-T scaffolds and 10% GelMA-T scaffolds loaded with BMSCs (10% GelMA-T/BMSCs) were transplanted into a defect site of nasal septum cartilage in a rabbit model. At 4, 12, and 24 weeks after surgery, the nasal septum cartilage defects exhibited more complete repair in rabbits treated with the 10% GelMA-T/BMSC scaffold according to hematoxylin & eosin, safranine-O, and toluidine blue staining. We showed that GelMA-T/BMSCs can be applied for the physiological and structural repair of defects in the nasal septum cartilage, providing a potential strategy for repairing cartilage defects in the clinic.